اعتماد البخاري قرينة السماع في رد وقبول الروايات: مختارات من أبواب الطهارة - حفيظي، حكيمة أحمد; عومارة، سهام Omarah, Seham; مشاقبة، عبدالرحمن (جامعة شريف هداية الله الإسلامية الحكومية - كلية الدراسات الإسلامية والعربية, 2022)
أجمع علماء الحديث على أن سماع الراوي عن شيخه، قرينة قوية تدل على اتصال السند، وأنها أعلى درجات التحمل في إثبات الاتصال بين الراوي ومن روى عنه، لأن من شروط الحديث الصحيح أن يرويه العدل الضابط عن مثله متصلا من غير انقطاع في السند؛ لذلك أولاها الأئمة النقاد عناية فائقة في الحكم على الرواية وصلا أو انقطاعا، وكان البخاري من أبرز الأئمة النقاد الذين اشترطوا السماع، سواء في جامعه الصحيح، أو في كتبه الأخرى كالتاريخ الكبير، أو فيما نقله عنه تلميذه الإمام الترمذي في جامعه، وفي علله الكبير؛ فكثيرا ما كان يسأله عن رأيه في الروايات، فيجيبه قبولا بإثبات سماع الراوي من شيخه، أوردا بنفي السماع بينهما؛ الأمر الذي يؤكد على أهمية هذه المسألة، وعلى أهمية بحثها؛ فاخترنا أن يكون بحثنا متعلقا بإبراز هذه المسألة عند الإمام البخاري، من خلال ما نقله عنه تلميذه الإمام الترمذي في أبواب الطهارة، من كتابيه "العلل الكبير" و"الجامع"، لذلك اعتمدنا في تحريره، المنهج الاستقرائي عند جمع النماذج المذكورة في الدراسة، والمنهجين التحليلي والنقدي عند دراسة الأقوال، وتحليلها، ونقدها، وانتهينا إلى مجموعة من النتائج أهمها: أن نفي السماع أو إثباته، يعد من أبرز القرائن الدالة على اتصال الإسناد أو انقطاعه، وأن الإمام البخاري اعتمد هذه القرينة في قبول الروايات وردها، في أكثر النماذج من هذه الأبواب، حتى نسب إليه عدم اكتفائه بالمعاصرة بين الرواة، بل ضرورة اللقاء بيهم، ومن بين النتائج التي انتهى إليها البحث، أن الإمام البخاري، يدعم في بعض الروايات، فيما انتقيناه من نماذج، قرينة إثبات السماع أو نفيه، في قبول الرواية أو ردها، بقرائن أخرى، تبين ما في هذه الروايات من علل. Hadith scholars agree on the fact that a narrator hearing a saying from his shaikh is strong evidence of the sanad connection. They also agree that this condition has the highest degree of endurance in proving the connection between the narrator and those who narrated from him. That’s why critic Imams have caringly and carefully used it in judging whether a narration is continuous or disconnected. And Imam al-Bukhari was among those who stipulated hearing as a condition for authenticity, whether in his collective Sahih or his other books like “the Great History” (Attarikh Alkabir) or what was reported from him by his student Imam Al-Tirmidhi in his Al-Ilal Alkabir book, as the latter often asked his Shaikh about his opinion on narrations and he answered him with acceptance or denial based on lack of evidence of hearing between the narrator and his Shaikh, which emphasises the importance of this matter and its research. This is why this research’s objective is to highlight this issue according to Imam Al-Bukhari through what his student Al-Tirmidhi reported from him in the chapters on purification (Attahara), in his two books Al-Ilal Al-Kabir and Al- Jami. Three methods are used in this paper: The inductive method was adopted when collecting the examples mentioned in the study, and the analytical and critical approaches when studying the sayings. Three important conclusions can be mentioned. First, denying or proving that a narrator heard a saying with his own ears is one of the most prominent clues that indicate the connection of the narration chain or its interruption. Second, that Imam al-Bukhari relied on this presumption in accepting and refuting the narrations in most examples of these chapters. Thirdly, that sometimes Imam al-Bukhari does not rely on the presumption of hearing alone in the authentification of the narration, but rather supports it with other evidence.
Keywords: المذاهب الإسلامية -- علماء الحديث -- دلالات النقل -- الاسنادات الصحيحة